Prophylactic antibiotics reduce hospitalisations and cost in locally advanced head and neck cancer patients treated with chemoradiotherapy: A randomised phase 2 study. (May 2019) - Ham, Janneke C.; Driessen, Chantal M.; Hendriks, Mathijs P.; Fiets, Edward; Kreike, Bas; Hoeben, Ann; Slingerland, Marije; van Opstal, Claudia C.; Kullberg, Bart Jan; Jonker, Marianne A.; Adang, Eddy M.; Kaanders, Johannes H.; et al.
Abstract: Background: Platinum-based chemoradiotherapy for locally advanced head and neck cancer (LAHNC) induces a high rate of acute toxicity, including dysphagia and aspiration pneumonia. We hypothesised that prophylactic antibiotics can prevent pneumonia and hospitalisations and can be cost-effective. Patient and methods: In this multicentre randomised trial, patients with LAHNC treated with chemoradiotherapy received prophylactic amoxicillin/clavulanic acid from day 29 after the start of treatment until 14 days after completion of chemoradiotherapy or standard care without prophylaxis. The primary objective was to observe a reduction in pneumonias. Secondary objectives were to evaluate the hospitalisation rate, adverse events, costs and health-related quality of life. Results: One hundred six patients were included; of which, 95 were randomised: 48 patients were allocated to the standard group and 47 patients to the prophylaxis group. A pneumonia during chemoradiotherapy and follow-up until 3.5 months was observed in 22 (45.8%) of 48 patients in the standard group and in 22 (46.8%) of 47 patients in the prophylaxis group ( p  = 0.54). Hospitalisation rate was significantly higher in the standard group versus the prophylaxis group, 19 of 48 pts (39.6%) versus 9 of 47 pts (19.1%), respectively ( p  = 0.03). Significantly more episodes with fever of any grade were observed in the standard group (29.2% vs 10.2%, p  = 0.028). A significant difference in costs was found, with an average reduction of €1425 per patient in favour of the prophylaxis group. Conclusion: Although prophylactic antibiotics during chemoradiotherapy for patients with LAHNC did not reduce the incidence of pneumonias, it did reduce hospitalisation rates and episodes with fever significantly and consequently tended to be cost-effective. Highlights: Chemoradiotherapy for locally advanced head and neck cancer induces many toxicities. Dysphagia and aspiration pneumonia are common side-effects. Prophylactic antibiotics reduce hospitalisation rate and are cost-effective.